The effect of female portrayal in advertising on the Palestinian females purchase decision. Issue 2 (17th May 2019) - Salem, Mohammed Z.; Baidoun, Samir; Walsh, Grace; Sweidan, Netham
Abstract : Purpose: The purpose of this study is to examine the impact of female portrayal in advertisements on Palestinian female consumers' purchasing decisions. TV and online media were selected as the medium for the study. Specifically, the researchers examine the one-dimensional sexualized female portrayal in advertisements. Design/methodology/approach: Culture is used as the lens through which the study examines the relationship between independent and dependent variables concerning the topic of this study. The study collected primary data from 395 Palestinian participants through a survey questionnaire. Findings: The findings of the study revealed that there is a relationship between the independent variable (the sexualized female portrayal in foreign advertisements – advertisements originating in foreign countries) and the dependent variable (Palestinian female consumers' purchase decision). Additionally, the study found that the cultural differences between Palestine and other foreign countries have a negative impact on the Palestinian female consumers' perception of the product being advertised. Practical implications: Although traditional marketing procedures would allow companies to filter and adapt particular adverts to suit various cultural, social and political environments, the advent of the open web and satellite TV channels extend the advertisements reach to audiences beyond their intended demographic. Originality/value: This is the first study set in the Arab context (including Palestine) to explore the impact of sexualized female portrayal in advertisements on Palestinian female consumers' purchasing decision.